Revisão e reescrita textual no ensino de língua portuguesa nos anos iniciais: um olhar para os documentos educacionais - Onofre, Jaqueline de Freitas (2021)
In light of Bakhtinian assumptions about dialogism, speech and utterance, this research seeks to investigate if/how the educational documents of Basic Education guides the curriculum of the city of Foz do Iguaçu – Paraná, at federal, state and county levels, propose the work revision and textual rewriting for Portuguese language classes. This research is justified by the need to investigate and affirm/deny whether there are assertive guidelines for the teacher that contribute to their work of correcting texts in Portuguese Language classes, especially in early years of elementary school. Thus, we listed the following research questions: do the educational documents, which guide the curriculum of Elementary School I in the county of Foz do Iguaçu, propose the work of textual revision and rewriting? If proposed, how do these guidelines occur? This research is, therefore, of a qualitative nature, with a basic and descriptive purpose, considering the socio-historical-discursive character proposed by Bakhtin and his Circle, and uses Dialogic Discourse Analysis (DDA) as a guideline under the Bakhtinian bias. Based on the ADD, we analyze how the status of revision and rewriting of texts in these documents occurs, in order to provide Portuguese Language teachers with theoretical and methodological guidelines that enable them to have a greater understanding of textual-interactive revision and enable them to streamline corrections of texts in the classroom. As a result, we consider that there is a lack of educational documents regarding guidelines on what can be reviewed in written production. We also observed that the documents under study do not present a theoretical bias regarding the moment of revision and textual rewriting and that, in some documents, uncertain/inaccurate guidelines and directions for the teacher appear.